Linguocolor picture of the world as an imprint of ethnoculture (Kulpina V.G. Linguistic Сolorology: from Рistory to the Рresent of Сolor Сonceptospheres. Moscow: MAKS Press, 2019. 288 p.) (Proceedings of Southern Federal University. Philology, 2020)
REVIEWS